Teachers' instructional efficacy and Korean students academic performance - Camit, Anne Cruz (2007)
This study was conducted to determine the relationship between the instructional efficacy of teachers and the academic performance of Korean students. The study employed a mixed method approach in research, namely the concurrrent triangulation strategy. Instructional efficacy was measured using researcher-made instruments: the Instructional Efficacy Questionnaire (IEQ), Performance Evaluation Questionnaire (PEQ) and Interview Schedule. The participants were Filipino teachers who conduct classes to entry level Korean students in a Makati language institute. The investigation supported the previous researches made on instructional efficacy and its relation with academic performance, a concept taken from Albert Bandura's self-efficacy.